2015
DOI: 10.1063/1.4930886
|View full text |Cite
|
Sign up to set email alerts
|

Phase ordering of zig-zag and bow-shaped hard needles in two dimensions

Abstract: We perform extensive Monte Carlo simulations of a two-dimensional bent hard-needle model in both its chiral zig-zag and its achiral bow-shape configurations and present their phase diagrams. We find evidence for a variety of stable phases: isotropic, quasi-nematic, smectic-C, anti-ferromorphic smectic-A, and modulated-nematic. This last phase consists of layers formed by supramolecular arches. They create a modulation of the molecular polarity whose period is sensitively controlled by molecular geometry. We id… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 83 publications
2
10
0
Order By: Relevance
“…It has been also detected in zero-thickness zig-zag and bow-shaped systems [26]. In addition, in [26,30,31] the authors have observed that upon increasing pressure, before the system attains antiferroelectric smectic A phase, a spatially non-uniform, bend-deformed polar domains with the overall zero net polarization are being formed.…”
Section: Introductionmentioning
confidence: 91%
“…It has been also detected in zero-thickness zig-zag and bow-shaped systems [26]. In addition, in [26,30,31] the authors have observed that upon increasing pressure, before the system attains antiferroelectric smectic A phase, a spatially non-uniform, bend-deformed polar domains with the overall zero net polarization are being formed.…”
Section: Introductionmentioning
confidence: 91%
“…One of valuable tools in such studies are computer simulations, such as Monte Carlo sampling (MC) and Molecular Dynamics (MD), which have a long-standing tradition in the investigation of structural properties of LC phases using a diverse range of models ranging from simplified lattice systems to fully atomistic ones [29][30][31] . Generally, the anisotropic shape of BSMs can be approximated in the simulations either by V-like or C-like bent objects (reflecting the C 2v symmetry) composed of i.a., needles [32][33][34] , spheres [35][36][37][38] , or spherocylinders [39][40][41][42] . It has been shown that those systems, each one separately, produce a wealth of interesting nematic and smectic phases.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous work we have investigated the phase ordering of bent needles with varying shape. 29 Our work is motivated by a recent experimental study of Fang et al 1 on the glasslike orientational dynamics of a self-assembled monolayer of photo-switching molecules. After aligning the molecules with light, the authors observed the decay of orientational order (or birefringence) under either thermal erasure or erasure with circularly polarized (CP) light.…”
Section: Introductionmentioning
confidence: 99%